Pengembangan Industri Halal: Rantai Nilai, Sertifikasi, dan Strategi Menjadi Pusat Halal Dunia - Abdul Aziz; Abdul Husenudin; Azkia Zahratunnisa; Asya Khoerunnisa; Haura Alya Taufiq; Amin Putriana (As-Syirkah: Islamic Economic & Financial Journal, 2025)
The halal industry has evolved into a strategic economic sector that extends beyond religious considerations to encompass competitiveness, consumer trust, and global value chain integration. Indonesia, as the country with the largest Muslim population, holds significant potential to become a global halal hub. However, this potential is still constrained by several challenges, particularly in strengthening the halal value chain and ensuring the effective implementation of halal certification, especially among regional micro, small, and medium enterprises (MSMEs). This study aims to analyze the role of the halal value chain and halal certification in supporting the development of the halal industry in Indonesia, with a specific focus on the Bogor region as a representative MSME halal food cluster. The research adopts a qualitative descriptive approach through a comprehensive literature review of academic books and reputable national and international journal articles, including Scopus-indexed publications, published up to 2025. The findings indicate that an integrated halal value chain, supported by credible halal certification and adequate halal logistics systems, plays a crucial role in enhancing the competitiveness of the halal industry. Nevertheless, a gap remains between national policy frameworks and their implementation at the regional level, particularly in terms of halal standard awareness, technological readiness, and stakeholder collaboration. This study contributes conceptually to the halal industry literature and provides practical implications for strengthening halal industry ecosystems at both regional and national levels.